Impact of boron foliar fertilization on annual fluctuation of B in sweet cherry leaves and fruit quality - Nagy, P. T.; Thurzó, T.; Szabó, Z.; Nyéki, J. (International Journal of Horticultural Science, 2008)
The goal of the study was to examine response of sweet cherries (Prunus avium L.) to boron (B) fertilization. The experiment was conducted during 2005-2007 in West Hungary on mature cv. `Germersdorfi 3’ grafted on Prunus mahaleb rootstock. Sweet cherry trees planted on a calcareous chernozem soil. Trees were foliar-fertilized with B. Foliar B sprays were performed: (1) in the spring, at the stage of white bud, beginning of flowering (B1), and (2) repeated 5 weeks after full bloom (B2). In each of spring spray treatments, B was applied at a rate of 0.15 kg ha-I. Trees untreated with B served as a control. The results showed that B fertilization had effect on B concentration in leaf tissues, mostly after ripening. B was present significantly higher amount in leaf in treated samples after ripening. Mean fruit weight was slightly increased by B fertilization. Fruit sensitivity to cracking was not influenced by B fertilization. Nevertheless, from our data it can be conclude that the sensitivity of fruit to cracking is improved when the fruit is riper, the fruit density and fruit weight are higher. The soluble solids varied between 15.0 and 15.9% according to the treatments. Our results for the monosaccharides investigated varied between 5.1 and 7.2 as glucose and fructose as well. Galactose and sucrose was detected very small amount in the unprocessed cherries. Applied B treatments increased sugar contents but decreased organic acid contents in sweet cherry fruits. It is concluded that under conditions of this experiment, B fertilization can be recommended in sweet cherry culture to improve fruit quality and their appearance.